From Poverty, Inequality to Smart City Proceedings of the National Conference on Sustainable Built Environment 2015 - Seta, Fumihiko; Sen, Joy.; Biswas, Arindam; Khare, Ajay.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book is a comprehensive document visualizing the future of built environment from a multidisciplinary dimension, with special emphasis on the Indian scenario. The multidisciplinary focus would be helpful for the readers to cross-refer and understand others' perspectives. The text also includes case studies substantiating theoretical research. This method of composition helps the book to maintain rational balance among theory, research and its contextual application. The book comprises selected papers from the National Conference on Sustainable Built Environment. The chapters provide varied viewpoints on the core issues of urbanization and planning, especially in the economically diverse Indian market. This compilation would be of interest to students, researchers, professionals and policy makers.
PART 1: Poverty, Inequality and urban infrastructure -- Municipal Solid Waste Management: A Paradigm to Smart Cities -- Urban Poverty: Trends, Assessment and Inclusive Planning as a Solution -- Influence of Changing Real Estate Scenarios on Affordable Housing in India -- Market Situation of Unauthorized Colonies in East Delhi: A Case Study of Guru Ram Dass Nagar -- PART 2: Smart city and Eco-city -- Smart Concepts for Integrated Rurban Development of Historical Towns in India: Case of Panipat, Haryana -- Analysis of Major Parameters of Smart Cities and their Suitability in Indian Context -- Re-defining and Exploring the Smart-City Concept in Indian Perspective: Case study of Varanasi -- Smart Cities and Disaster -- Indian smart cities and their financing: A First Look -- Evaluating the Effect of Building Envelope on Thermal Performance of Houses in Lower Himachal Pradesh -- Eco City or Environmentally Sustainable Villages -- Potential of Energy Saving at the City Level through Energy Efficient Buildings: A Study in the Context of Ahmedabad City.
Keywords: Sustainability; Civil engineering; Human geography; Engineering design; Sustainability; Civil Engineering; Human Geography; Engineering Design